The Role of Parents in Children's Sexual Education in Pintu Khimbe Village, Lawe Alas District, Southeast Aceh Regency - Sriwahyuni, Endang (DEEP LEARNING: Journal of Educational Research, 2025)
Free sex is one of the social phenomena in Pintu Khimbe Village that is very concerning. This problem is closely related to the role of parents as educators for their children, and among these roles is providing sexual education to children from an early age. The purpose of this research in this thesis is to determine the efforts and roles of parents in Pintu Khimbe Village in implementing sexual education for children, as well as the obstacles faced by parents in carrying out their roles. This study uses a descriptive quantitative approach. The population of this study was 250 heads of families, and samples were taken randomly as much as 10% of the population, namely 25 parents. Data collection was carried out using interview techniques with 5 children, and questionnaires to 25 parents. Data from interview observations were analyzed through three stages, namely data reduction, data presentation, drawing conclusions. The data from the questionnaire were analyzed using a percentage formula. The results of the study that the author obtained were that the role of parents in children's sexual education in Pintu Khimbe Village was to provide sufficient religious education to children, provide moral education, provide education to reason, provide social education, and provide physical education. Parents' efforts in implementing children's sexual education are by controlling their children at school and outside of school, giving advice to children to want to live clean and healthy, teaching the boundaries of what is allowed and what is not allowed when in friendship. The obstacles faced by parents in implementing sexual education for children are the lack of free time with children, the inability to control the media watched by children and the lack of verbal ability in answering children's questions about "sensitive" issues that children should know.